Covalent organic framework material with hydrogen-bond interaction sites as well as preparation method and application of covalent organic framework material
By modifying phosphate or amidoxime on covalent organic framework materials, the problems of small adsorption, slow rate, poor selectivity and poor circulation performance of uranium extracting materials in seawater in the prior art are solved, and efficient and fast Uranium adsorption and good cycling performance.
Patent Information
- Application Number
- CN202411788158.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art faces the problems of small adsorption amount, slow adsorption rate, poor selectivity and poor cyclability when extracting uranium from seawater, especially when interfering ions exist, the adsorption amount retention rate of the material is low.
The chemical and thermal stability of the material is improved by using a covalent organic framework material with hydrogen bonding sites and enhanced its adsorption ability to uranyl carbonate ions through modification of phosphate groups or amidoxime groups. This material optimizes the structure and performance of the material by collaboratively controlling raw materials, raw material ratio, process and process parameters.
It significantly improves the adsorption amount and adsorption rate of uranium, reaches adsorption equilibrium within 10 minutes, and the adsorption amount exceeds 100mg g-1, and maintains high selectivity when uranium and vanadium plasma coexist, and the extraction amount of uranium can still reach 86%. above. After 10 cycles of the material, the adsorption retention rate is still above 87%.
Smart Images

Figure CN119409917A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of functionalized materials, and in particular to a covalent organic framework material with hydrogen bonding sites, a preparation method and an application thereof. Background Art
[0002] Uranium in seawater mainly exists in the form of uranyl carbonate ions. Existing technical reports on the extraction of uranium from seawater mainly focus on uranyl ions. In the actual environment, uranyl ions are closely combined with carbonate ions, which increases the difficulty of extracting uranium from seawater. The existing preparation methods of uranyl carbonate ion adsorption materials are complicated, and the prepared materials have poor adsorption effects, including small adsorption capacity, slow adsorption rate, poor selectivity and poor recyclability. The composite adsorbent MXene-AO@LZU1 (Stable and highly efficient extraction of U(VI)from seawater bycovalent organic frameworks and amidoxime co-functionalizedMXene) prepared by electrostatic self-assembly of transition metal carbides and nitrides with a stable covalent organic framework requires three steps of reaction to be prepared. Its uranium adsorption capacity in uranyl carbonate solution is about 22 mg g -1 , adsorption equilibrium can be obtained in 30 minutes. When interfering ions coexist with uranyl carbonate ions, taking vanadium as an example, the adsorption retention rate of MXene-AO@LZU1 is only 33%. In addition, the existing public covalent materials are cycled ≤5 times, and the adsorption retention rate after the cycle is ≤85%. Therefore, it is a technical problem that needs to be solved urgently to prepare materials with fast adsorption rate, large adsorption amount, high selectivity, good thermal stability, and good recyclability, and not destroy the structure of covalent organic matter during the adsorption process. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a covalent organic framework material with hydrogen bonding sites, wherein the covalent organic framework material with hydrogen bonding sites is a covalent organic framework material with hydrogen bonding sites grafted with a phosphate group or a covalent organic framework material with hydrogen bonding sites grafted with an amine oxime group;
[0004] The preparation method of the covalent organic framework material having hydrogen bonding sites grafted with phosphate groups comprises the following steps:
[0005] Raw materials A and B are mixed, added to solvent C, stirred at room temperature for 0.5-5h, and then added with C solution of COF material containing imine bond, wherein the molar ratio of COF material containing imine bond, A and B is 1:5:1-1:200:100, and the concentration of COF material containing imine bond in solvent C is 0.001-0.05mol L -1 , and then perform 2-10 cycles of treatment, each cycle of treatment is: freezing in liquid nitrogen for 3-10 minutes, vacuuming for 3-10 minutes, filling with nitrogen, and then thawing at room temperature, and then reacting at 25-150°C for 24-120 hours, washing and drying overnight to obtain a covalent organic framework material with hydrogen bonding sites grafted with phosphate groups;
[0006] The preparation method of the covalent organic framework material having hydrogen bonding sites grafted with amidoxime groups comprises the following steps:
[0007] The cyano-grafted COF material and hydroxylamine hydrochloride are added to a mixed solution containing triethylamine and solvent G according to a molar ratio of 1:20-1:2, wherein the volume ratio of triethylamine to solvent G is 1:200-1:50, and the concentration of the cyano-grafted COF material in solvent G is 0.01-0.1 mol L -1 , reacting at 45-100° C. for 12-72 hours, washing and drying to obtain a covalent organic framework material having hydrogen bonding sites grafted with amine oxime groups;
[0008] The preparation method of the cyano-grafted COF material comprises the following steps:
[0009] Raw materials D and E are mixed, added to solvent F, stirred at room temperature for 0.5-5h, and then a mixed solution of COF material containing imine bonds and solvent F is added, wherein the molar ratio of the COF material containing imine bonds, D and E is 1:5:1-1:200:100, and the concentration of the COF material containing imine bonds in solvent F is 0.001-0.05 mol L -1 , and then perform 2-10 cycles of treatment, each cycle of treatment is: freezing in liquid nitrogen for 3-10 minutes, vacuuming for 3-10 minutes, filling with nitrogen, and then thawing at room temperature, and then reacting at 25-150°C for 24-120h, and then washing and drying overnight to obtain a cyano-grafted COF material;
[0010] The preparation method of the COF material containing imine bonds comprises the following steps:
[0011] After tri(4-benzoyl)amine and p-phenylenediamine were mixed in a molar ratio of 3:1, a mixed solution of o-dichlorobenzene and ethanol was added, and after ultrasonication for 5 minutes, an acetic acid solution was added; three vacuum cycle treatments were performed, and each cycle treatment was: freezing in liquid nitrogen for 5 minutes, vacuuming for 5 minutes, filling with nitrogen, and then thawing at room temperature, and then reacting under vacuum at 120°C for 3 days, and then washing and drying to obtain a COF material containing an imine bond (referred to as IISERP-COF2), wherein the volume ratio of o-dichlorobenzene to ethanol was 1:1, and the concentration of the acetic acid solution was 3 mol L -1 ;
[0012] The A is one of trimethylsilyl bromide or sodium borohydride;
[0013] The B is one of diethyl phosphite or acetic acid;
[0014] The solvent C is one of acetonitrile or ethanol;
[0015] The D is one of 4-acetylenebenzonitrile and 1,4-dinitrosobenzene;
[0016] The E is one of methanol or a mixture of chlorobenzoquinone and boron trifluoride etherate, and the molar ratio of chlorobenzoquinone to boron trifluoride etherate is 1:1-3:1;
[0017] The solvent F is one of toluene or tetrahydrofuran;
[0018] The solvent G is one of N,N-dimethylacetamide or ethanol;
[0019] The covalent organic framework material with hydrogen bonding sites has a 5% thermal weight loss temperature of ≥200°C, a water contact angle of ≤50°, and a water vapor adsorption capacity of 4-25cm 3 g -1 , the adsorption of uranium in uranyl carbonate solution is >100 mg g -1 The adsorption equilibrium time is ≤10min. The material has strong selective adsorption. When uranium and vanadium plasma coexist, the uranium extraction amount can still be ≥86% of that of single uranium. After 10 cycles of use, the adsorption retention rate is ≥87%;
[0020] Furthermore, the water contact angle of the covalent organic framework material with hydrogen bonding sites is 10-48.6°, and the adsorption amount of uranium in uranyl carbonate solution is 103-300 mg g -1 .
[0021] The present invention provides application of a covalent organic framework material with hydrogen bonding sites in the field of uranium extraction from seawater.
[0022] Compared with the prior art, the present invention coordinates and regulates raw materials, raw material ratios, processes and process parameters, and only within the scope of protection of the claims of the present invention, the obtained covalent organic framework material has good binding ability to uranyl carbonate ions, large adsorption capacity, fast adsorption rate, strong selectivity, and good recyclability. The specific analysis is as follows: First, the covalent organic framework material modified with phosphate and amine oxime groups provided by the present invention has good chemical and thermal stability and can maintain thermal stability above 200°C; second, the material obtained by the present invention has strong hydrophilicity, a water contact angle of ≤50°, and a water vapor adsorption capacity of 4-25cm 3 g -1 Third, the uranium adsorption capacity of the materials obtained by the present invention is higher than that of the prior art materials, and the adsorption speed is significantly improved. The uranium adsorption capacity of the materials in the uranyl carbonate solution is >100 mg g -1 , and the adsorption rate is fast, and the adsorption equilibrium can be reached in 10 minutes. Compared with COF-DG (Guanidinium-based ionic covalent organic frameworks for capture of uranyl tricarbonate) reported by Wang et al., the equilibrium time of the covalent organic framework materials modified by phosphate and amine groups is shortened by 400 times, and the adsorption amount is increased by 3.8 times and 1.5 times respectively; fourthly, the material obtained by the present invention has strong selectivity, and even when uranium and vanadium plasma coexist, it can still have a strong adsorption effect on uranyl carbonate ions, and the extraction amount of uranium can still be ≥86% of that of single uranium; fifthly, the material obtained by the present invention has good recycling performance. After 10 cycles of use, the adsorption amount of the material obtained by the present invention can still be maintained at a rate of more than 87%, while the material obtained by the prior art can only be recycled 5 times, and the retention rate is only 85%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0024] Figure 1 This is a comparison chart of the grafting rates of the post-modified covalent organic framework materials prepared in Examples 1-4;
[0025] Figure 2 a, 2b and 2c are scanning electron microscopic comparison images of IISERP-COF2, IISERP-COF2-PO3H2-2 obtained in Example 2 and IISERP-COF2-AO-2 prepared in Example 4, respectively;
[0026] Figure 3 It is a comparison diagram of infrared spectra of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2, and IISERP-COF2-AO-2 prepared in Example 4;
[0027] Figure 4 It is a comparison chart of X-ray powder diffraction spectra of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2, and IISERP-COF2-AO-2 prepared in Example 4;
[0028] Figure 5 5a, 5b and 5c are water contact angle comparison diagrams of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2 and IISERP-COF2-AO-2 prepared in Example 4, respectively;
[0029] Figure 6 This is the thermogravimetric spectrum of IISERP-COF2-PO3H2-2 prepared in Example 2;
[0030] Figure 7 This is the thermogravimetric spectrum of IISERP-COF2-AO-2 prepared in Example 4;
[0031] Figure 8 This is a comparison chart of nitrogen adsorption of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2, and IISERP-COF2-AO-2 prepared in Example 4;
[0032] Fig. 9 This is a comparison diagram of water vapor adsorption-desorption experiments at 298K for IISERP-COF2-PO3H2-2 prepared in Example 2 and IISERP-COF2-AO-2 prepared in Example 4;
[0033] Fig.10 This is a comparison chart of the adsorption effects of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2, and IISERP-COF2-AO-2 prepared in Example 4 on uranyl carbonate ions;
[0034] Fig.11 This is the ion selectivity diagram of IISERP-COF2-PO3H2-2 prepared in Example 2;
[0035] Fig.12 This is a bar chart showing that IISERP-COF2-PO3H2-2 prepared in Example 2 achieved 10 cycles of utilization. DETAILED DESCRIPTION
[0036] The post-modification method and application of the covalent organic framework material provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0037] Tri(4-benzoyl)amine (20 mg, 0.06 mmol) and p-phenylenediamine (10.5 mg, 0.09 mmol) were added to a 10 ml Pyrex tube, and a mixed solution of o-dichlorobenzene and ethanol (the volume ratio of o-dichlorobenzene and ethanol was 1:1) was added. After ultrasonic treatment for 5 minutes, 0.15 mL of acetic acid (concentration was 3 M) was added. Three vacuum cycles were performed, each of which was: freezing in liquid nitrogen for 5 minutes, vacuuming for 5 minutes, filling with nitrogen, and then thawing at room temperature, and then reacting under vacuum at 120°C for 3 days, and then washing and drying to obtain a COF material with an imine bond (IISERP-COF2).
[0038] The obtained IISERP-COF2 was subjected to a uranyl carbonate ion adsorption experiment: 1 mg of IISERP-COF2 was added to 100 mL of uranyl ammonium carbonate aqueous solution (10 ppm) and the uranium adsorption test was carried out at room temperature for one hour. The uranium concentration in the solution was tested using a UV-visible photometer, and the adsorption amount of IISERP-COF2 was 33 mg g -1 , and the adsorption equilibrium can be reached in 30min. XRD test shows that IISERP-COF2 has an ordered structure, and the water contact angle test shows that its water contact angle is 79.2°, which means that its hydrophilicity is poor.
[0039] Example 1
[0040] Trimethylsilyl bromide (528 μL, 4 mmol) was added to a solution of diethyl phosphite (130 μL, 1 mmol) in anhydrous acetonitrile (1 mL), stirred at room temperature for 2 hours, and then a solution of IISERP-COF2 (14 mg, 0.1 mmol) in anhydrous acetonitrile (1 mL) was added. Three vacuum cycles were performed, each of which was: freezing in liquid nitrogen for 5 minutes, vacuuming for 5 minutes, filling with nitrogen, and then thawing at room temperature. After reacting at room temperature for 3 days, the product was washed and dried overnight to obtain a COF material grafted with a phosphate group (IISERP-COF2-PO3H2-1), and the grafting rate of the phosphate group was 48%.
[0041] Example 2
[0042] Trimethylsilyl bromide (2640 μL, 20 mmol) was added to a solution of diethyl phosphite (650 μL, 5 mmol) in anhydrous acetonitrile (3 mL), stirred at room temperature for 2 hours, and then a solution of IISERP-COF2 (14 mg, 0.1 mmol) in anhydrous acetonitrile (3 mL) was added. Three vacuum cycles were performed, each of which was: freezing in liquid nitrogen for 5 minutes, vacuuming for 5 minutes, filling with nitrogen, and then thawing at room temperature. After reacting at room temperature for 3 days, the product was washed and dried overnight to obtain a COF material grafted with a phosphate group (IISERP-COF2-PO3H2-2), and the grafting rate of the phosphate group was 74%.
[0043] The IISERP-COF2-PO3H2-2 obtained in Example 2 was subjected to a uranyl carbonate ion adsorption experiment: 1 mg of IISERP-COF2-PO3H2-2 was added to 100 mL of an aqueous solution of uranyl ammonium carbonate (10 ppm), and a uranium adsorption test was performed at room temperature for one hour. The uranium concentration in the solution was tested using a UV-visible photometer. The adsorption amount of IISERP-COF2-PO3H2-2 was 254 mg g. -1 The time to reach adsorption equilibrium is 10 min.
[0044] XRD tests revealed that IISERP-COF2-PO3H2-2 has an ordered pore structure, with a water contact angle of 23.5° and a water vapor adsorption capacity of 21.6 cm 3 g -1, which can effectively accommodate water vapor molecules, indicating that the material has good hydrophilicity and is conducive to full contact with uranyl carbonate ions in aqueous solution. The reported UiO66-3C4N (A Bio-inspired Nano-pocket Spatial Structure for Targeting Uranyl Capture) is prepared by introducing 4-aminoisophthalic acid into UiO-66, and its water contact angle is about 28°, and its hydrophilicity is worse than that of IISERP-COF2-PO3H2-2. It takes 10 hours for it to reach adsorption equilibrium in a solution containing uranyl carbonate ions, while the time for IISERP-COF2-PO3H2-2 obtained in the present invention to reach adsorption equilibrium is shorter, only 10 minutes, and the adsorption rate is faster. The uranium adsorption test shows that IISERP-COF2-PO3H2-2 has good ion selectivity. Ti3C2-AO-PA (Highly efficient extraction of uranium from seawater by polyamide and amidoxime co-functionalized MXene) is prepared by introducing amidoxime groups on the surface of Ti3C2 by hydrothermal method. The uranium / vanadium selectivity of IISERP-COF2-PO3H2-2 is 5 times that of Ti3C2-AO-PA. The presence of vanadium in the solution has little effect on the adsorption of uranium by IISERP-COF2-PO3H2-2 obtained by the present invention. IISERP-COF2-PO3H2-2 has a broader application prospect in complex environmental systems. At the same time, the structurally stable IISERP-COF2-PO3H2-2 has good cycle performance. The number of cycles of the covalent organic material obtained by the prior art is ≤5 times, and the adsorption retention rate of the material on uranium after the cycle is ≤85%. IISERP-COF2-PO3H2-2 can be recycled for 10 times or more, and the adsorption retention rate is above 87%.
[0045] Example 3
[0046] 4-Ethynylbenzonitrile (127 mg, 1 mmol), boron trifluoride etherate (80 μL, 0.6 mmol) and tetrachlorobenzoquinone (160 mg, 0.6 mmol) were added to 5 mL of toluene and stirred at room temperature for 2 hours, and then a toluene (5 mL) solution of IISERP-COF2 (29.2 mg, 0.2 mmol) was added. Three vacuum cycles were performed, each of which was: freezing in liquid nitrogen for 5 minutes, vacuuming for 5 minutes, filling with nitrogen, and then thawing at room temperature. The reaction was carried out at 110°C for 3 days. The product was washed and dried overnight to obtain IISERP-COF2-CN-1. IISERP-COF2-CN-1 (30 mg, 0.1 mmol), triethylamine (100 μL) and hydroxylamine hydrochloride (50 mg, 1 mmol) were added to 10 mL of ethanol. The mixture was reacted at 70° C. for 2 days, and the product was washed and dried overnight to obtain an amidoxime-grafted COF material (IISERP-COF2-AO-1) with an amidoxime grafting rate of 37%.
[0047] Example 4
[0048] 4-Ethynylbenzonitrile (635 mg, 5 mmol), boron trifluoride etherate (400 μL, 3 mmol) and tetrachlorobenzoquinone (800 mg, 3 mmol) were added to 20 mL of toluene and stirred at room temperature for 2 hours, and then a toluene (20 mL) solution of IISERP-COF2 (29.2 mg, 0.2 mmol) was added. Three vacuum cycles were performed, each of which was: freezing in liquid nitrogen for 5 minutes, vacuuming for 5 minutes, filling with nitrogen, and then thawing at room temperature. Reacted at 110°C for 3 days. The product was washed and dried overnight to obtain IISERP-COF2-CN-2. IISERP-COF2-CN-2 (30 mg, 0.1 mmol), triethylamine (100 μL) and hydroxylamine hydrochloride (50 mg, 1 mmol) were added to 10 mL of ethanol. The mixture was reacted at 70° C. for 2 days, and the product was washed and dried overnight to obtain an amidoxime-grafted COF material (IISERP-COF2-AO-2) with an amidoxime-grafting rate of 64%.
[0049] The IISERP-COF2-AO-2 obtained in Example 4 was subjected to a uranyl carbonate ion adsorption experiment: 1 mg of IISERP-COF2-AO-2 was added to 100 mL of uranyl ammonium carbonate aqueous solution (10 ppm), and the uranium adsorption test was carried out at room temperature for one hour. The uranium concentration in the solution was tested using a UV-visible photometer, and the adsorption amount of IISERP-COF2-AO-2 was 103 mg g -1, reaching adsorption equilibrium in 10 minutes. The prior art uses diaminoguanidine hydrochloride and 1,3,5-triformylphloroglucinol for Schiff base reaction, and designs and synthesizes the ionic covalent organic framework, COF-DG material. When conducting adsorption experiments, this material needs to attract uranyl carbonate anions through anion exchange, specifically through the coordination of hydroxyl and guanidine groups with uranyl ions for adsorption. This process needs to overcome the binding force between carbonate and uranyl ions; while the IISERP-COF2-AO-2 obtained by the present invention only adsorbs uranyl carbonate ions through hydrogen bonds, and does not need to destroy the coordination structure of carbonate and uranyl ions. The adsorption amount of IISERP-COF2-AO-2 is 1.5 times that of COF-DG. After XRD testing, it was found that IISERP-COF2-AO-2 still maintained an ordered pore structure, and the water contact angle test showed that its water contact angle was 48.6°, which was more hydrophilic than IISERP-COF2 (contact angle: 79.2°).
[0050] Structural characterization and performance analysis
[0051] Figure 1 is a comparison chart of the grafting rates of the post-modified covalent organic framework materials prepared in Examples 1-4, Figure 1 It can be seen that the phosphate group grafting rate of IISERP-COF2-PO3H2-1 prepared in Example 1 is 48%, and the phosphate group grafting rate of IISERP-COF2-PO3H2-2 prepared in Example 2 is 74%; the amine oxime group grafting rate of IISERP-COF2-AO-1 prepared in Example 3 is 37%, and the amine oxime group grafting rate of IISERP-COF2-AO-2 prepared in Example 4 is 64%.
[0052] Figure 2 a, 2b and 2c are scanning electron microscopic comparison images of IISERP-COF2, IISERP-COF2-PO3H2-2 obtained in Example 2 and IISERP-COF2-AO-2 prepared in Example 4, respectively. Figure 2 a It can be seen that the prepared IISERP-COF2 is spherical with a diameter of 1-2 nm. The scanning electron microscopy images of the phosphate- and amidoxime-modified covalent organic framework materials prepared in Examples 2 and 4 are as follows: Figure 2 a, they formed nanospheres with a diameter of 1-2 nm, indicating that the post-modification process obtained by the present invention does not change the material morphology and size.
[0053] Figure 3 The infrared spectra of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2 and IISERP-COF2-AO-2 prepared in Example 4 are compared. Figure 3It can be seen that the N–H stretching vibration peak (3200–3500 cm -1 ) disappeared, and the C=O vibration peak (1694cm -1 ) and C=N vibration peak (1592cm -1 ) proved the occurrence of Schiff base reaction; P=O(1177cm -1 ) and P–OH (1064 cm -1 ) vibration peaks proved the successful modification of the phosphate group; N–O (960cm -1 )The appearance of the stretching vibration peak proves the successful modification of the amine oxime group.
[0054] Figure 4 The X-ray powder diffraction spectra of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2 and IISERP-COF2-AO-2 prepared in Example 4 are compared. Figure 4 It can be seen that the three materials have characteristic peaks at 3.62°, 4.76° and 8.93°, indicating that the obtained IISERP-COF2-PO3H2-2 and IISERP-COF2-AO-2 maintain the ordered structure of IISERP-COF2, and the post-modification of the group does not destroy the crystallinity of the material.
[0055] Figure 5 5a, 5b and 5c are the comparison diagrams of water contact angles of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2 and IISERP-COF2-AO-2 prepared in Example 4, respectively. Figure 5 It can be seen that the water contact angle of IISERP-COF2 is 79.2°, the water contact angle of IISERP-COF2-PO3H2-2 is 23.5°, and the water contact angle of IISERP-COF2-AO-2 is 48.6°. The material obtained in the present invention forms hydrogen bonds with water molecules, which greatly improves the hydrophilicity of the material.
[0056] Figure 6 This is the thermogravimetric spectrum of IISERP-COF2-PO3H2-2 prepared in Example 2;
[0057] Figure 7 is the thermogravimetric spectrum of IISERP-COF2-AO-2 prepared in Example 4; Figure 6-7 It can be seen that the material prepared by the present invention has good thermal stability and remains thermally stable above 200°C;
[0058] Figure 8The nitrogen adsorption comparison diagram of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2 and IISERP-COF2-AO-2 prepared in Example 4 is shown in FIG. Figure 8 It can be seen that the specific surface areas of IISERP-COF2, IISERP-COF2-PO3H2-2 and IISERP-COF2-AO-2 are 754, 248 and 101 m 2 / g, and the pore sizes are 2.6, 1.76, and 1.78 nm, respectively. By adjusting the ratio of the grafted raw materials, more functional groups can be grafted into the pores of IISERP-COF2, and the pore size gradually decreases, forming pores that match the size of uranyl carbonate ions, which is beneficial to the adsorption of uranium.
[0059] Fig. 9 The water vapor adsorption-desorption experiment comparison diagram of IISERP-COF2-PO3H2-2 prepared in Example 2 and IISERP-COF2-AO-2 prepared in Example 4 at 298K is shown in FIG. Fig. 9 It can be seen that the water vapor adsorption capacity of IISERP-COF2-PO3H2-2 and IISERP-COF2-AO-2 prepared in the present invention is 21.6 and 4.9 cm 3 g -1 . In the water vapor adsorption-desorption curves of the two materials, an obvious hysteresis loop phenomenon was found. The appearance of the hysteresis loop refers to the phenomenon that the adsorption branch and the desorption branch of the adsorption isotherm of gas on porous solids are separated. The large hysteresis loop proves that the material has a strong hydrogen bonding interaction ability with water molecules. This shows that IISERP-COF2-PO3H2-2 and IISERP-COF2-AO-2 have the potential to form hydrogen bonds with the carbonate in the uranyl carbonate ion, which is beneficial to their adsorption of uranyl carbonate.
[0060] Fig.10 The adsorption effect of IISERP-COF2, IISERP-COF2-PO3H2-2 prepared in Example 2 and IISERP-COF2-AO-2 prepared in Example 4 on uranyl carbonate ion is compared. Fig.10 It can be seen that the adsorption capacity of IISERP-COF2 is 33 mg g -1 , and the adsorption equilibrium can be reached in 30 min. The IISERP-COF2-PO3H2-2 and IISERP-COF2-AO-2 prepared by the present invention can reach the adsorption equilibrium in the ammonium uranyl carbonate solution in 10 min, and the adsorption amounts are 254 and 103 mg g, respectively. -1The IISERP-COF2-PO3H2-2 and IISERP-COF2-AO-2 obtained by the present invention adsorb uranyl carbonate ions through hydrogen bonds and have a high grafting rate, so that more functional groups are fixed in IISERP-COF2, so that the adsorption amount of IISERP-COF2-PO3H2-2 and IISERP-COF2-AO-2 is higher than that of the existing reported materials.
[0061] Fig.11 The ion selectivity diagram of IISERP-COF2-PO3H2-2 prepared in Example 2 is shown in FIG. Fig.11 It can be seen that the phosphate-modified covalent organic framework material prepared by the present invention has good ion selectivity. Taking vanadium as an example, when uranyl carbonate ions and vanadium acyl ions coexist, vanadium does not affect the adsorption of uranium by the material of the present invention, and the extraction amount of uranium remains at 86% of the original, which is equivalent to 5 times the extraction amount of the covalent material in the prior art.
[0062] Fig.12 The IISERP-COF2-PO3H2-2 prepared in Example 2 was recycled 10 times. After the adsorption was completed, the uranium adsorbed in the IISERP-COF2-PO3H2-2 was washed away by sodium bicarbonate and nitric acid solution, and then the next adsorption test was performed. Fig.12 It can be seen that IISERP-COF2-PO3H2-2 has good recyclability. After 10 cycles, the adsorption retention rate is still above 87%.
[0063] In summary, compared with the prior art, the present invention coordinately regulates raw materials, raw material ratios, processes and process parameters, and only within the protection scope of the claims of the present invention, the covalent organic framework material obtained has good binding ability for uranyl carbonate ions, large adsorption capacity, fast adsorption rate, strong selectivity, good thermal stability and recyclability, which are superior to the covalent materials obtained by the prior art; the specific analysis is as follows: first, the covalent organic framework material modified with phosphate and amine oxime groups provided by the present invention has good chemical and thermal stability (it can still maintain thermal stability above 200°C); second, the material obtained by the present invention has strong hydrophilicity, a water contact angle of ≤50°, and a water vapor adsorption capacity of 4-25cm 3 g -1 Third, the uranium adsorption capacity of the materials obtained by the present invention is higher than that of the prior art materials, and the adsorption speed is significantly improved. The uranium adsorption capacity of the materials in the uranyl carbonate solution is >100 mg g -1, and the adsorption rate is fast, and the adsorption equilibrium can be reached in 10 minutes. Compared with the COF-DG reported by Wang et al., the equilibrium time of the covalent organic framework materials modified with phosphate and amine groups obtained by the present invention is shortened by 400 times, and the adsorption amount is increased by 3.8 and 1.5 times respectively; fourthly, the material obtained by the present invention has strong selectivity, and even when uranium and vanadium ions coexist, it can still have a strong adsorption effect on uranyl carbonate ions, and the extraction amount of uranium can still be ≥86% of the single uranium; fifthly, the material obtained by the present invention has good recycling performance. After 10 cycles of use, the adsorption amount of the material obtained by the present invention can still be maintained at a rate of more than 87%, while the material obtained by the prior art can only be recycled 5 times, and the retention rate is only 85%.
Claims
1. A covalent organic framework material having hydrogen bonding sites, wherein the covalent organic framework material having hydrogen bonding sites is a covalent organic framework material having hydrogen bonding sites grafted with a phosphate group or a covalent organic framework material having hydrogen bonding sites grafted with an amine oxime group; The preparation method of the covalent organic framework material having hydrogen bonding sites grafted with phosphate groups comprises the following steps: Raw materials A and B are mixed, added to solvent C, stirred at room temperature for 0.5-5h, and then added with C solution of COF material containing imine bond, wherein the molar ratio of COF material containing imine bond, A and B is 1:5:1-1:200:100, and the concentration of COF material containing imine bond in solvent C is 0.001-0.05mol L -1 , and then perform 2-10 cycles of treatment, each cycle of treatment is: freezing in liquid nitrogen for 3-10 minutes, vacuuming for 3-10 minutes, filling with nitrogen, and then thawing at room temperature, and then reacting at 25-150°C for 24-120 hours, washing and drying overnight to obtain a covalent organic framework material with hydrogen bonding sites grafted with phosphate groups; The preparation method of the covalent organic framework material having hydrogen bonding sites grafted with amidoxime groups comprises the following steps: The cyano-grafted COF material and hydroxylamine hydrochloride are added to a mixed solution containing triethylamine and solvent G according to a molar ratio of 1:20-1:2, wherein the volume ratio of triethylamine to solvent G is 1:200-1:50, and the concentration of the cyano-grafted COF material in solvent G is 0.01-0.1 mol L -1 , reacting at 45-100° C. for 12-72 hours, washing and drying to obtain a covalent organic framework material having hydrogen bonding sites grafted with amine oxime groups; The preparation method of the cyano-grafted COF material comprises the following steps: Raw materials D and E are mixed, added to solvent F, stirred at room temperature for 0.5-5h, and then a mixed solution of COF material containing imine bonds and solvent F is added, wherein the molar ratio of the COF material containing imine bonds, D and E is 1:5:1-1:200:100, and the concentration of the COF material containing imine bonds in solvent F is 0.001-0.05 mol L -1 , and then perform 2-10 cycles of treatment, each cycle of treatment is: freezing in liquid nitrogen for 3-10 minutes, vacuuming for 3-10 minutes, filling with nitrogen, and then thawing at room temperature, and then reacting at 25-150°C for 24-120h, and then washing and drying overnight to obtain a cyano-grafted COF material; The preparation method of the COF material containing imine bonds comprises the following steps: After tri(4-benzoyl)amine and p-phenylenediamine were mixed in a molar ratio of 3:1, a mixed solution of o-dichlorobenzene and ethanol was added, and after ultrasonication for 5 minutes, an acetic acid solution was added; three vacuum cycle treatments were performed, and each cycle treatment was: freezing in liquid nitrogen for 5 minutes, vacuuming for 5 minutes, filling with nitrogen, and then thawing at room temperature, and then reacting under vacuum at 120°C for 3 days, and then washing and drying to obtain a COF material containing an imine bond (referred to as IISERP-COF2), wherein the volume ratio of o-dichlorobenzene to ethanol was 1:1, and the concentration of the acetic acid solution was 3 mol L -1 ; The A is one of trimethylsilyl bromide or sodium borohydride; The B is one of diethyl phosphite or acetic acid; The solvent C is one of acetonitrile or ethanol; The D is one of 4-acetylenebenzonitrile and 1,4-dinitrosobenzene; The E is one of methanol or a mixture of chlorobenzoquinone and boron trifluoride etherate, and the molar ratio of chlorobenzoquinone to boron trifluoride etherate is 1:1-3:1; The solvent F is one of toluene or tetrahydrofuran; The solvent G is one of N,N-dimethylacetamide or ethanol; The covalent organic framework material with hydrogen bonding sites has a 5% thermal weight loss temperature of ≥200°C, a water contact angle of ≤50°, and a water vapor adsorption capacity of 4-25cm 3 g -1 The adsorption of uranium in uranyl carbonate solution is >100 mg g -1 The adsorption equilibrium time is ≤10min, the material has strong selective adsorption effect, and when uranium and vanadium plasma coexist, the uranium extraction amount can still be ≥86% of the single uranium. After 10 cycles of use, the adsorption retention rate is ≥87%.
2. The covalent organic framework material having hydrogen bonding sites according to claim 1, characterized in that: The water contact angle of the covalent organic framework material with hydrogen bonding sites is 10-48.6°, and the adsorption amount of uranium in uranyl carbonate solution is 103-300 mg g -1 .
3. Application of the covalent organic framework material having hydrogen bonding sites as claimed in claim 1 or 2 in the field of uranium extraction from seawater.